Growth and yield response of shallot (Allium ascalonicum L. var. Tuktuk) from different source materials applied with liquid biofertilizers - Jhon Hardy Purba; PUTU SRI WAHYUNI; ZULKARNAEN ZULKARNAEN; NANANG SASMITA; I GUSTI AYU DIAH YUNITI; NI PUTU PANDAWANI (Nusantara Bioscience, 2020)
Abstract. Purba JH, Wahyuni PS, Zulkarnaen, Sasmita N, Yuniti IGD, Pandawani NP. 2020. Growth and yield response of shallot (Allium ascalonicum L. var. Tuktuk) from different source materials applied with liquid biofertilizers. Nusantara Bioscience 12: 127-133. This research was to examine growth and yield of shallots using different sources of propagation material, namely true shallot seed (TSS) and bulbs. Soil biological fertility, which was generally low, was improved by the addition of liquid organic fertilizer. The purpose of this study a) to determine the differences in the propagation of plants from seeds and bulbs of shallot Tuktuk varieties, and b) to determine the effect of liquid biofertilizer maxigrow and rhizobacteria. The study used a one-factor randomized design. The results showed that the growth and yield of shallots propagated with bulbs were better than the origin of the seeds. The treatment of the two types of liquid biofertilizer produces tangible growth and yield, but there was no significant difference between the two kinds of liquid organic fertilizer.